2004
DOI: 10.1111/j.1439-0434.2004.00910.x
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal of Venturia inaequalis Ascospores and Disease Gradients from a Defined Inoculum Source

Abstract: Aerial concentration of ascospores of Venturia inaequalis and incidence of apple scab were monitored in an orchard during the ascospore release seasons in 1999, 2000 and 2001 on susceptible (Jonagold) and moderately resistant (Schone van Boskoop) apple cultivars. A 1-ha orchard was divided into an inoculum source block (approximately 0.34 ha) and an inoculum-free block (approximately 0.66 ha) where inoculum was excluded by covering the soil surface with polythene sheets. Ascospore numbers and disease incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Additionally, an IBD pattern was detected within each of these two subpopulations. Our work represents a rare example in pathogens where the dispersal evaluated by a fine scale IBD pattern appropriately fits with previously reported empirical field data [16,53]. Because many pathogen dispersal capabilities remain unclear, our validation of the IBD approach is particularly significant for epidemiologists and also has practical implications for plant breeders and landscape managers for the design of disease control strategies.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Additionally, an IBD pattern was detected within each of these two subpopulations. Our work represents a rare example in pathogens where the dispersal evaluated by a fine scale IBD pattern appropriately fits with previously reported empirical field data [16,53]. Because many pathogen dispersal capabilities remain unclear, our validation of the IBD approach is particularly significant for epidemiologists and also has practical implications for plant breeders and landscape managers for the design of disease control strategies.…”
Section: Discussionsupporting
confidence: 70%
“…Second, IBD detection across this orchard highlighted restricted V. inaequalis dispersal over space. Holb et al [16] showed that the mean daily ascospore count in traps at 21 metres and 45 metres was approximately one-third and one-tenth of the sexual spores trapped at the source, respectively, highlighting that a substantial number of ascospores could travel at least 45 metres from the inoculum source. Lower dispersal abilities were previously reported by Kaplan [53] who observed that 99% of the spores are not able to spread more than 5 or 6 metres.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conidial dispersal is a key factor in the spread of diseases within crops and is affected by water splash from rain or irrigation water and also by wind and air currents (16,17,21,22). The environment in a mushroom-growing room is very uniform and considerably different from that in greenhouses or outdoors, since the crop is grown indoors, in closed rooms, under very specific conditions of temperature, humidity, and air speed, delivered through an air-conditioning system (2,15).…”
mentioning
confidence: 99%